CITRA POLITIK PRABOWO-SANDI DALAM PEMILIHAN PRESIDEN (PILPRES) 2019 DI AKUN MEDIA SOSIAL INSTAGRAM - Maulina, Putri; Muttaqin, Muttaqin (Interaksi: Jurnal Ilmu Komunikasi, 2020)
Prabowo Subianto and Sandiaga Uno are one of the candidate pairs as Presidential and Vice President Election candidates in the 2019 Presidential Election. In this event, there was many strategies used by the candidates to attracting public electability. The aims of this study is to determine the image of  Prabowo-Sandi's in the political branding process that showed in instagram @indonesiaadilmakmur. This study used the Semiotic Analysis approach to look the meaning of political image which represented in instagram @indonesiaadilmakmur and the Political Branding concept that focused in three indicators: Appearance, Personality and Political Key Message. The method used in this study is semiotic analysis by Charles Peirce  with a qualitative approach in interpretive paradigm. Finally, th results of this study found that the process of Prabowo-Sandi’s branding formed through three indicators political branding such Appearance, Personality, and Political Key Message in generally are depicted as personal figure of religious, assertive, hard, patriot, polite, calm, integrity, smart and close to society.